The Key Barrier to Digital Transformation in Pakistan's Construction Sector - Waheed, Muhammad; Abbas, Mutahir (MultiTech Publisher, 2023)
Digitalization has become a global trend and the Pakistani construction industry is no exception. Digitalization has faced many challenges over the years. The objective of this study is to uncover the obstacles preventing the adoption of digitalization within the Pakistani construction industry. Additionally, it aims to analyze the advantages that digitalization offers in enhancing productivity within this sector. The results show that the main barriers to digitalization are barriers related to the use of technology, the high cost of technology, lack of energy, ease of replacement, and unavailability of digital equipment. Stakeholders' awareness of the benefits of digitalization needs to be increased.